MENENTUKAN PELUANG DAN PERIODE ULANG GEMPA DENGAN MAGNITUDE TERTENTU BERDASARKAN MODEL GUTTENBERG - RITCHER - Zera, Tati (Jurnal Spektra, 2014)
A simple model of earthquake prediction can be constructed based on Magnitude and cumulative frequenty relation by Guttenberg - Richter equation. It is carried out a probability determinated simulation and quake repetition period with a certain magnitude to examine the model. Executing the model to 204 earthquakes data with > 5 RS of magnitude and > 100 km hypocentre which occured in January 1910 to January 2010 in West Java region at 60 â 80Â N and 1050Â â 1090 W, shown that the earthquake with low magnitude has shorter repetition period and bigger probability to occur. On the other hand the earthquake with higher magnitude has longer repetition period and has small probability to occur. By conducting the model test, it is obtained the seismicity index, a = 9,46 and the rock resistance, b = 1.265, which is showing the resistance of that region to a quake. The highest repetition periods (100 years) = 99,9% is in 3rdarea with 19 year and seismicity index for highest quake is 1.38.Keywords: Earthquake Prediction, Guttenberg-Ritcher, seismicity index, rock resistance.